TEMAN (Tablet Effervescent Manggis) Pengembangan Dan Pengolahan Ekstrak Kulit Manggis Menjadi Effervescent Sebagai Suplement Kesehatan Ditinjau Dari Faktor Eksternal - Ferdinand, Stephen (SINOMIKA Journal: Publikasi Ilmiah Bidang Ekonomi dan Akuntansi, 2022)
Starting from the people's desire for health supplements that are safe and practical and can also increase endurance, especially during the current covid-19 pandemic, many people want health supplements that are rich in benefits and taste delicious, fresh and can be consumed daily on a daily basis. routine. TEMAN is in a growth and build position using a market penetration strategy and there are two main strategies chosen based on the IE Matrix and SWOT Matrix, the first to do online and offline promotions, the second to build their own factory according to standards. In the business environment, the factors that can affect the company are divided into two aspects, namely the remote environment and the industrial environment. Millennials are targeted to work actively and care about health but do not have enough time with a product strategy that can be marketed online and offline. to support the company's strategy, namely online and offline promotions, the pricing structure is carried out by TEMAN which will later be able to see financial projections, investment feasibility analysis and also financial performance analysis. Risk management activities must be able to create and protect added value for TEMAN.